Progranulin Inhibits Human T Lymphocyte Proliferation by Inducing the Formation of Regulatory T Lymphocytes - Kyu Hwan Kwack; Hyeon-Woo Lee (Mediators of Inflammation)
We have examined the effect of progranulin (PGRN) on human T cell proliferation and its underlying mechanism. We show that PGRN inhibits the PHA-induced multiplication of T lymphocytes. It increases the number of iTregs when T lymphocytes are activated by PHA but does not do so in the absence of PHA. PGRN-mediated inhibition of T lymphocyte proliferation, as well as the induction of iTregs, was completely reversed by a TGF-β inhibitor or a Treg inhibitor. PGRN induced TGF-β secretion in the presence of PHA whereas it did not in the absence of PHA. Our findings indicate that PGRN suppresses T lymphocyte proliferation by enhancing the formation of iTregs from activated T lymphocytes in response to TGF-β.